Antibiotic Resistance of Pathogens Causing Community-Acquired Pneumonia - Feldman, Charles; Anderson, Ronald (Seminars in Respiratory and Critical Care Medicine, 2012)
Community-acquired pneumonia remains an important cause of disease and death in both developed and developing countries and therefore continues to have a major medical impact. The mortality remains high despite the ready availability of potent antimicrobial agents to which the organisms are susceptible. However, management of these infections is potentially complicated by the emerging resistance of many of the common pathogens to the different classes of antibiotics that are usually prescribed. Furthermore, it is also being recognized that antibiotic resistance or treatment failures may occur not only through traditional microbial antibiotic resistance mechanisms but also through less well defined mechanisms, particularly those developed by the microbes in relation to their quorum sensing/biofilm machinery. Much recent research in this field has been focused on evaluating the clinical impact of antibiotic resistance on optimal antibiotic treatment and antimicrobial choices, as well as alternative strategies to deal with antibiotic resistance and treatment failures.
Keywords: antibiotic resistance; β-lactam antibiotics; biofilm formation; community-acquired pneumonia; fluoroquinolones; macrolides; quorum sensing